2010
DOI: 10.1136/emj.2009.082693
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemia modified albumin cannot be used for rapid exclusion of acute coronary syndrome

Abstract: This study does not support the use of IMA as a negative predictor for ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…This method has been developed to determine IMA in the setting of cardiac ischemia, which could improve the sensitivity of diagnosing ACS. Although some studies supported the use of IMA in patients presenting symptoms of ACS (12,(23)(24)(25), the others did not support the use of IMA alone in the diagnosis of ACS or AMI (26)(27)(28)(29)(30). IMA levels in our study are consistent with some previous reports, that serum IMA levels of patients with AMI were significantly higher than those of healthy subjects.…”
Section: Ami Patiens Controlssupporting
confidence: 76%
“…This method has been developed to determine IMA in the setting of cardiac ischemia, which could improve the sensitivity of diagnosing ACS. Although some studies supported the use of IMA in patients presenting symptoms of ACS (12,(23)(24)(25), the others did not support the use of IMA alone in the diagnosis of ACS or AMI (26)(27)(28)(29)(30). IMA levels in our study are consistent with some previous reports, that serum IMA levels of patients with AMI were significantly higher than those of healthy subjects.…”
Section: Ami Patiens Controlssupporting
confidence: 76%
“…However, the area under curve of ROC curve of IMA was not good enough and might not be a good candidate for diagnosis of myocardial infarction. The lack of diagnostic potential of IMA was also mentioned in many studies [1,21,22]. However, our results showed that combinatorial determination of these two biomarkers gave not good enough for NSTEMI diagnosis as it, although it slightly increased NPV and test efficiency.…”
Section: Discussionmentioning
confidence: 48%
“…This suggests that IMA levels may not be useful as a diagnostic indicator in the differential diagnosis of acute coronary syndrome in the emergency department. Previous studies reported that IMA had good accuracy (66% to 95%) but low specificity (13% to 45%) for the diagnosis of patients with acute coronary syndrome (16)(17)(18), although IMA may not be used to reliably exclude the diagnosis of acute coronary syndrome in the emergency department (19,20). IMA may be a guide as to whether to perform further investigation for acute coronary syndrome in patients admitted to the emergency department with chest pain, analogous to D-dimer testing in the diagnostic algorithm for pulmonary embolism (21,22).…”
Section: Discussionmentioning
confidence: 99%